15% of Talar Osteochondral Lesions Are Present Bilaterally While Only 1 in 3 Bilateral Lesions Are Bilaterally Symptomatic. (21st September 2022) - Rikken, Quinten G.H.; Wolsink, Lisanne M.E.; Dahmen, Jari; Stufkens, Sjoerd A.S.; Kerkhoffs, Gino M.M.J.
Abstract : Background: The primary aim of the present study was to determine the prevalence of osteochondral lesions of the contralateral talus in patients with computed tomography (CT)-confirmed osteochondral lesions of the talus (OLT). The secondary aims were to determine if the contralateral lesions were symptomatic and to describe the demographic characteristics and radiographic presentation of patients with bilateral OLT. Methods: To identify patients with bilateral OLT, we utilized a cross-sectional database of consecutive patients with a CT-proven OLT who had undergone bilateral CT scanning at our hospital between January 1989 and June 2021. The primary outcome was the prevalence of bilateral OLT. Patients with bilateral OLT were grouped into a unilaterally symptomatic group and a bilaterally symptomatic group. Patient and lesion characteristics were compared between these groups as well as between the symptomatic and asymptomatic ankles in the unilaterally symptomatic group. Radiographic examination included lesion volume, location, and morphology. Results: Of 1, 062 patients with OLT, 161 (15%) had bilateral OLT. Of the patients with bilateral OLT, 53 (33%) were bilaterally symptomatic. Patients who were bilaterally symptomatic were younger (p = 0.03) and more likely to present with a non-traumatic etiology (p < 0.01) in comparison with those who were unilaterally symptomatic. No differences were observed between the unilaterally and bilaterally symptomatic groups in terms of lesion morphology, volume, or location. In the unilaterally symptomatic group, lesion volume was significantly larger in symptomatic ankles in comparison with the contralateral, asymptomatic ankles (p < 0.01), but no significant differences were observed in terms of lesion morphology or location. Conclusions: In patients presenting with symptomatic OLT, the prevalence of bilateral OLT was 15%, and 1 in 3 patients with bilateral OLT were symptomatic on both sides. Larger lesion volume was associated with the presence of symptoms in patients with bilateral OLT. For patients with bilateral OLT, the treating team should be aware that younger patients and patients without a history of trauma are at a higher risk for having bilateral symptoms. Level of Evidence: Prognostic Level III . See Instructions for Authors for a complete description of levels of evidence.